Analisis Kesulitan Membaca Permulaan pada Siswa Kelas 1 SDN Kuin Utara 7 - Nurbaiti Rahmah; Ahmad Suriansyah; Arta Mulya Budi Harsono; M. Ziyan Takhqiqi Arsyad; Rianti Yulandra (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The purpose of this study is to examine the initial reading challenges faced by first-grade students at SDN Kuin Utara 7. It does this by analyzing the challenges in initial reading, identifying the factors that contribute to these challenges, and identifying the steps that teachers can take to help their students become better readers. Three methods of gathering data were used in this qualitative study: student interviews, instructor interviews, and observation. Five first-graders were among the study's participants. Five first-graders at SDN Kuin Utara 7 were categorized as poor in the first reading ability group, according to the study's results. Poor letter identification, halting or less fluent reading, and speech issues including stuttering were among the challenges encountered. Both internal and external factors contribute to these challenges.